Improves Children's Ability In Learning To Read And Write Through The RERIRO Method For Slow Learners - Apryani, Dwi Surami; Listiowati, Martiana Putri; Husna, Maulida Fitria; Rachmawati, Umi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine whether the use of the RERIRO method can improvereading and writing skills in Slow Learners at SD N Keditan. This research was carriedout in one of the classes of SD N Keditan, namely class IV and apply experiments usingthepaper roll game Researcher's suggested that the RERIRO method can be used inteaching to improve reading and writing skills in children with slow learner. The resultsof the study indicate that there is an increase in the results of children in reading andwriting.Elementary school teachers to using the RERIRO method as a bridge in teachingreading and writing, especially in Indonesian subjects.It can make students moreinterested in learning activities that are being carried out.